2006
DOI: 10.1086/504593
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Kiloparsec-Scale Radio Outflows in Radio-Quiet Active Galactic Nuclei

Abstract: Seyfert galaxies commonly host compact jets spanning 10-100 pc scales, but larger structures are resolved out in long-baseline aperture synthesis surveys. Previous, targeted studies showed that kiloparsec-scale radio structures ( KSRs) may be a common feature of Seyfert and LINER galaxies, and the origin of KSRs may be starbursts or active galactic nuclei (AGNs). We report a new Very Large Array survey of a complete sample of Seyfert and LINER galaxies. Out of all of the surveyed radio-quiet sources, we find t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
264
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(293 citation statements)
references
References 197 publications
(356 reference statements)
24
264
4
1
Order By: Relevance
“…Similarly, Cicone et al (2014) reported the ratio of the kinetic energy of the outflow to the AGN bolometric luminosity in 14 low-z luminous AGNs (including ULIRGs) is up to 5%, also based on CO observations. The value of this ratio is close to predicted value from theoretical model for explaining the M BH − σ relation in local galaxies (e.g., Silk & Rees Weaver et al 2010;(8) Dasyra et al 2011;(9) Gallimore et al 2006;(10) 1.4 GHz data from Nagar et al 2005;(11) FIRST catalog (Faint Images of the Radio Sky at Twenty-cm); (12) Sramek 1975;(13) 4.89 GHz data from Laurent-Muehleisen et al 1997;(14) 1.4 GHz data from Condon et al 1998;(15) Bicay et al 1995;(16) Taylor et al 2006;(17) 4.89 GHz data from Ulvestad & Wilson 1984;(18) 4.85 GHz data from Gregory et al 1994;(19) de Vaucouleurs et al 1991, RC3 (Third Reference Catalog of Bright Galaxies), photographic magnitude; (20) 4680Å data from Petrosian et al 2007; (21) 1998; King 2010). Therefore, it is likely that powerful AGN-driven outflows can give impacts on NLR clouds and consequently cause fast shocks in NLRs.…”
Section: 4supporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, Cicone et al (2014) reported the ratio of the kinetic energy of the outflow to the AGN bolometric luminosity in 14 low-z luminous AGNs (including ULIRGs) is up to 5%, also based on CO observations. The value of this ratio is close to predicted value from theoretical model for explaining the M BH − σ relation in local galaxies (e.g., Silk & Rees Weaver et al 2010;(8) Dasyra et al 2011;(9) Gallimore et al 2006;(10) 1.4 GHz data from Nagar et al 2005;(11) FIRST catalog (Faint Images of the Radio Sky at Twenty-cm); (12) Sramek 1975;(13) 4.89 GHz data from Laurent-Muehleisen et al 1997;(14) 1.4 GHz data from Condon et al 1998;(15) Bicay et al 1995;(16) Taylor et al 2006;(17) 4.89 GHz data from Ulvestad & Wilson 1984;(18) 4.85 GHz data from Gregory et al 1994;(19) de Vaucouleurs et al 1991, RC3 (Third Reference Catalog of Bright Galaxies), photographic magnitude; (20) 4680Å data from Petrosian et al 2007; (21) 1998; King 2010). Therefore, it is likely that powerful AGN-driven outflows can give impacts on NLR clouds and consequently cause fast shocks in NLRs.…”
Section: 4supporting
confidence: 87%
“…Such active galactic nuclei (AGNs) emit huge radiative energy. In addition to the strong radiation, AGNs sometimes show strong outflows in various forms that are recognized as the radio jet (e.g., Wilson & Willis 1980;Gallimore et al 2006), broad absorption-line (BAL) feature (e.g., Weymann et al 1991;Gibson et al 2009), ultra-fast outflow (UFO; e.g., Cappi 2006;Tombesi et al 2010), and so on. The released radiative and mechanical energies are expected to give significant impacts on vari-ous properties of the inter-stellar medium (ISM) in host galaxies, that may lead to the termination of the starforming activity.…”
mentioning
confidence: 99%
“…Therefore, the radio feature in NGC 7479 is most likely driven by the active nucleus, whereas the radio structure in NGC 3079 is driven by the central starburst. Other radio lobes/outflow features among nearby edge-on spiral galaxies are seen, e.g., in the Sombrero galaxy NGC 4594 and in NGC 4235 (Gallimore et al 2006).…”
Section: Comparison To Other Nearby Spiral Galaxies With Large-scale mentioning
confidence: 94%
“…Error bars represent measurement uncertainties, except for NGC 5548 where they reflect variability. NVSS Condon et al (1998), FIRST Becker et al (1995), CO96 Colbert et al (1996), OR10 Orienti & Prieto (2010), ED87 Edelson (1987), KU95 Kukula et al (1995), LA04 Lal et al (2004), and GA06 Gallimore et al (2006). 'map' stands for the map obtained from the VLA archive.…”
Section: Beam Sizes and Variabilitymentioning
confidence: 99%